Topic and influence analysis on technological patents related to security vulnerabilities. Issue 128 (May 2023) - Charmanas, Konstantinos; Mittas, Nikolaos; Angelis, Lefteris
Abstract: Security vulnerabilities have become a rapidly growing threat for various industries and application users. To overcome these issues and maintain their products' credibility, organizations and individuals develop mitigating techniques that are patented for copyright protection. The goal of this study is to extract and synthesize knowledge about patented inventions that address weaknesses of information systems and are generally deployed by firms to maintain security from potential breaches. To achieve this goal, we apply a variety of techniques based on text mining and citation network analysis. The applied methodologies lead in reviewing the current state, depicting relations between the innovations, identifying the general topics extracted from the patents' descriptions and assessing the firms' positioning in the technological field of security vulnerabilities. The findings can be used as knowledge map for determining current trends, assessing innovation, developing novel ideas and conduct studies regarding products and competitors related to security vulnerabilities.